(untitled) (Journal of actual problems of jurisprudence, 2018)
The article gives a theoretical analysis of measures of state coercion, observance of the principle of inviolability of the person when applying measures of criminal procedural coercion. The purpose of this study is to examine issues directly related to the mechanism for implementing measures of criminal procedural coercion in criminal proceedings; actualize the problem in question and the need for its further resolution by legal means; strengthening of procedural guarantees of the principle of inviolability of the person in the Criminal Procedure Code of the Republic of Kazakhstan, etc. Achievement of the set goal is facilitated by the following tasks: identification of the category of the inviolability of the individual as a human right in a democratic state; the ratio of international legal norms and legislation of the Republic of Kazakhstan regulating the right to inviolability of the person; analysis of the norms of the Constitution of the Republic of Kazakhstan on the human right to personal freedom as the basis of the principle of inviolability of the person; legal assessment of the inviolability of the individual as a category of criminal procedural science, the principle of criminal procedural legislation; determination of types of guarantees for the realization of the inviolability of the person when applying measures of procedural coercion. The logical, formal, legal, analytical, as well as functional method, which reveals the qualitative characteristics of the research subject, allows to determine the essence of the institution under study, the possibility of the regulatory impact of the constitutional and sectoral legislation on the state of law and order in the Republic of Kazakhstan is used to study the questions posed. As a result of research the system of theoretical positions in the field of guarantees and realization of the principle of inviolability of the individual, which is called to provide the basis of democratic transformations in the Republic of Kazakhstan, is grounded. Guarantees of the implementation of these rights by citizens, which can give the state, are, in the opinion of the author, first of all, in a reliable and developed legislative framework that meets the realities of life. Key words: coercive measures, measures of criminal procedural coercion, the principle of inviolability of the person, detention, arrest, guarantees of the implementation of the principle of inviolability of the person